N-acetylglucosaminyltransferase II Is Involved in Plant Growth and Development Under Stress Conditions - Yoo, Jae Yong; Ko, Ki Seong; Vu, Bich Ngoc; Lee, Young Eun; Yoon, Seok Han; Pham, Thao Thi; Kim, Ji-Yeon; Lim, Jae-Min; Kang, Yang Jae; Hong, Jong Chan; Lee, Kyun Oh (Frontiers in Plant Science, 2021)
Alpha-1,6-mannosyl-glycoprotein 2--N-acetylglucosaminyltransferase (EC 2.4.1.143, N-acetylglucosaminyltransferase II [GnTII]) catalyzes the transfer of N-acetylglucosamine (GlcNAc) residue from the nucleotide sugar donor UDP-GlcNAc to the α1,6-mannose residue of the di-antennary N-glycan acceptor GlcNAc(Xyl)Man3(Fuc)GlcNAc2 in the Golgi apparatus. Although the formation of the GlcNAc2(Xyl)Man3(Fuc)GlcNAc2 N-glycan is known to be associated with GnTII activity in Arabidopsis thaliana, its physiological significance is still not fully understood in plants. To address the physiological importance of the GlcNAc2(Xyl)Man3(Fuc)GlcNAc2 N-glycan, we examined the phenotypic effects of loss-of-function mutations in GnTII in the presence and absence of stress, and responsiveness to phytohormones. Prolonged stress induced by tunicamycin (TM) or sodium chloride (NaCl) treatment increased GnTII expression in wild-type Arabidopsis (ecotype Col-0) but caused severe developmental damage in GnTII loss-of-function mutants (gnt2-1 and gnt2-2). The absence of the 6-arm GlcNAc residue in the N-glycans in gnt2-1 facilitated the TM-induced unfolded protein response (UPR), accelerated dark-induced leaf senescence, and reduced cytokinin signalling, as well as susceptibility to cytokinin-induced root growth inhibition. Furthermore, gnt2-1 and gnt2-2 seedlings exhibited enhanced NPA-induced inhibition of tropic growth and development. Thus, GnTII’s promotion of the 6-arm GlcNAc addition to N-glycans is important for plant growth and development under stress conditions, possibly via affecting glycoprotein folding and/or distribution.